Improvement Suggestion Of Solair Incinerator Waste Entry Door Size Specification And Position Using Hierarchy Of Control Framework - Dian Ayu Aprianti; Rino Andias Anugraha; Muhammad Iqbal (eProceedings of Engineering, 2015)
Abstract Awkward posture refers to positions of the body while performing work activities that deviate significantly from the neutral position and may pose risks such as damage traumatic work Musculoskeletal Disorders (MSDs). Solair incinerator controlled by one operator. The position of operator enter the waste indicates as awkward position. The existing work posture assessment score with RULA obtain 7. The value indicates that the working posture is necessary investigate and change immediately. Because the operator working with the hand(s) above the head, or the elbow(s) above the shoulders more than 2 hours total per day. This study focus on observation to work posture and the facility (entry door of incinerator) when operator enter the waste. The existing dimension of the entry door is L x W x H x D = 100 cm x 70 cm x 169 cm x 83 cm. The suggestion size is 80-101 cm for height. The waste container load 1-1.5kg with diameter 27 and height 40. And suggestion standard screw container is 9 inch. After analysis and get score 2 for the improvement size of incinerator entry door purpose to avoid the awkward position and reduce the risk of MSDs to the operator. Keywords: awkward position, incinerator entry door, musculoskeletal disorders (MSDs), RULA